DUKUNGAN ARSIP DALAM KONFLIK BATAS WILAYAH: Array - Sumrahyadi Sumrahyadi (Arsip Nasional Republik Indonesia, 2010)
Boundary region, nowadays, has become complicated problems not only in some districts or provinces areas but also in some countries. In many cases a district or a municipality as well a province claims other areas or regions to increase their income or to explore resources for their wealth. Similarly, in some countries, they claim other areas or islands as their belonging. To anticipate the possibility of a lawsuit the territory from other countries, they should be supported by records and archives, as sources of authentic information and legal evidence. From the experience of losing Sipadan and Ligitan islands to be part of Malaysia territory and other national cases, we need to document all activities properly and provide records and archives as an authentic evidence of the existence of certain areas or islands.